Machines like me : and people like you - McEwan, Ian (Nan A. Talese/Doubleday, 2019)
"Machines Like Me occurs in an alternative 1980s London. Britain has lost the Falklands War, Margaret Thatcher battles Tony Benn for power, and Alan Turing achieves a breakthrough in artificial intelligence. In a world not quite like this one, two lovers will be tested beyond their understanding. Charlie, drifting through life and dodging full-time employment, is in love with Miranda, a bright student who lives with a terrible secret. When Charlie comes into money, he buys Adam, one of the first batch of synthetic humans. With Miranda's assistance, he co-designs Adam's personality. This near-perfect human is beautiful, strong, and clever--a love triangle soon forms. These three beings will confront a profound moral dilemma. Ian McEwan's subversive and entertaining new novel poses fundamental questions: What makes us human? Our outward deeds or our inner lives? Could a machine understand the human heart? This provocative and thrilling tale warns against the power to invent things beyond our control"--